A wide field of view plasma spectrometer. Issue 7 (23rd July 2016) - Skoug, R. M.; Funsten, H. O.; Möbius, E.; Harper, R. W.; Kihara, K. H.; Bower, J. S.
Abstract: We present a fundamentally new type of space plasma spectrometer, the wide field of view plasma spectrometer, whose field of view is > 1.25 π ster using fewer resources than traditional methods. The enabling component is analogous to a pinhole camera with an electrostatic energy‐angle filter at the image plane. Particle energy‐per‐charge is selected with a tunable bias voltage applied to the filter plate relative to the pinhole aperture plate. For a given bias voltage, charged particles from different directions are focused by different angles to different locations. Particles with appropriate locations and angles can transit the filter plate and are measured using a microchannel plate detector with a position‐sensitive anode. Full energy and angle coverage are obtained using a single high‐voltage power supply, resulting in considerable resource savings and allowing measurements at fast timescales. We present laboratory prototype measurements and simulations demonstrating the instrument concept and discuss optimizations of the instrument design for application to space measurements. Key Points: WPS plasma spectrometer based on pinhole camera with electrostatic energy‐angle filter WPS provides fast measurements over nearly 2 pi field of view WPS measurements obtained for reduced resources